“Can my mother come?” Asylum interviews with unaccompanied and separated children seeking asylum in the Netherlands - Rap, Stephanie E. (Frontiers in Human Dynamics, 2023)
Introduction The UN Convention on the Rights of the Child (CRC) accords children the right to give their views on all important decisions in their life (art.12 CRC). In the past decades increased awareness has risen among professionals who work with children in judicial and administrative proceedings, to hear their voices. The key question guiding this research was whether refugee children have the possibility to meaningfully participate in asylum proceedings, as required by international children's rights law and standards? Asylum application procedures are highly complex administrative procedures, that are often not adapted to the capacities and level of maturity of children. Recent studies suggest that the right to participation and information is insufficiently safeguarded for children involved in asylum procedures. Unaccompanied children seeking asylum as young as 6 years of age have to go through the asylum procedure in the Netherlands. Efforts have been put in making this procedure more child-friendly, by designing a child-friendly interview room and training immigration officers. The aim of this study was to explore to what extent the immigration authority takes into account children's voice, age and development, in line with international children's rights. Methods Observations have been conducted of first instance asylum application interviews with children held by immigration officers. In total 13 interviews with children aged 7–11 have been observed, that were held between 2012 and 2019. Results The results show that child-friendly conversation techniques and tools are used to some extent, however, immigration officers should be trained more extensively in order to enhance the effective participation of young children. Discussion It is concluded that interviews with children could be improved by giving children more information and using techniques to communicate with young children. In order to truly hear the child's voice the interviews should be better adapted to the age and level of development of unaccompanied children.